Proceedings, fourth workshop on home sewage disposal in Colorado emphasizing state/county cooperation in managing small wastewater flows - Ward, Robert C., editor; Colorado Water Resources Research Institute, Colorado State University, publisher (Colorado State University. Libraries, 1981)
The 4th workshop on home sewage disposal in Colorado was held in 1981 at Colorado State University.
Keywords: Drainage, House -- Colorado -- Congresses; Septic tanks -- Colorado -- Congresses